A Unified Strategy Towards N‐Aryl Heterocycles by a One‐Pot Copper‐Catalyzed Oxidative C–H Amination of Azoles. Issue 27 (5th August 2014) - Subramanian, Parthasarathi; Kaliappan, Krishna P.
Abstract: An efficient one‐pot synthesis of N ‐aryl‐substituted heterocycles by a Cu‐catalyzed two‐fold C–N bond formation is reported. This strategy involves a Cu I ‐catalyzed C–N bond‐forming reaction between azoles and electron‐deficient bromopyridines followed by an intramolecular sp 2 C–H amination. One of the products thus formed has been successfully used as a ligand for the synthesis of a Pd complex. Abstract : An efficient one‐pot synthesis of N ‐aryl heterocycles by a Cu‐catalysed double C–N bond formation is reported. This strategy involves a Cu I ‐catalysed C–N bond‐forming reaction between azoles and electron‐deficient bromopyridines followed by an intramolecular sp 2 C–H amination.